A review on environmental chemodynamics, isothermal, kinetics, and thermodynamics modeling for the adsorptive removal of Cr(VI) from the industrial effluent using magnetic nanoparticles as a bio-sorbent - Nadarajah, Rekah; Hossain, Md. Sohrab; Mobin Siddique, Md Bazlul; Arafath, Md. Azharul; Naushad, Mu.; Lim, Jun Wei; Al-Gheethif, Adel; Ahmad, Harlina (2023)
The contamination of the hexavalent chromium [Cr(VI)] in the aquatic ecosystem poses environmental concerns due to its portable and highly poisonous nature. The implementation of magnetic bio-adsorbents has received immense consideration for the adsorptive elimination of Cr(VI) from industrial effluent, which is attributed to their high adsorption capability, manipulable reactive sites, high physicomechanical stability, high thermal stability, high surface area, and reusability. This study reviews the sources of Cr(VI) contamination, the chemodynamics of Cr(VI) in the environment, the synthesis of magnetic adsorbents and their implementation for Cr(VI) elimination from various types of wastewater, including industrial effluent. The adsorption behavior of the magnetic adsorbent was assessed by reviewing the isothermal, kinetics, and thermodynamics modeling of Cr(VI) adsorption using magnetic adsorbents. The results show that the magnetic adsorbents can be implemented as potential adsorbents for the elimination of Cr(VI) from wastewater and industrial effluents. These findings should be applicable in determining active bio-sorbents for the elimination of Cr(VI) from industrial effluent.